2021
DOI: 10.1371/journal.pone.0251157
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative cerebral oximetry in open heart surgeries reduced postoperative complications: A retrospective study

Abstract: Cardiothoracic surgeries are life-saving procedures but often it results in various complications. Intraoperative cerebral oximetry monitoring used to detect regional cerebral oxygen saturation (rScO2) is a non-invasive method that provides prognostic importance in cardiac surgery. The main aim of the present study was to evaluate the association of intraoperative cerebral oxygen monitoring during cardiac surgery on postoperative complications. This was a case-controlled retrospective study conducted on adult … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…A study proves that preserving blood flow to the brain has lesser adverse outcomes post-open-heart surgery [25]. Maintaining cerebral blood perfusion will ensure a stable blood flow to the brain.…”
Section: Discussionmentioning
confidence: 94%
“…A study proves that preserving blood flow to the brain has lesser adverse outcomes post-open-heart surgery [25]. Maintaining cerebral blood perfusion will ensure a stable blood flow to the brain.…”
Section: Discussionmentioning
confidence: 94%
“…Another single-center prospective trial examining NIRS-directed intraoperative interventions (including fluid challenge, deepening anesthesia, and administration of vasoactive medications) during episodes of cerebral oxygen desaturation (< 60% for > 60 consecutive seconds) during CPB found that 6 months postoperative group mean memory change scores were significantly improved in the intervention group, although overall perioperative outcomes did not differ between intervention and control groups ( 181 ). Likewise, a retrospective study evaluating association of intraoperative cerebral oxygen monitoring during cardiopulmonary bypass on postoperative complications found that cerebral oximetry monitoring during cardiothoracic surgery was associated with lower incidence of stroke and overall mortality rate ( 182 ).…”
Section: Postoperative Vascular Dysfunction and Organ Damage: ...mentioning
confidence: 99%
“…Therefore, real-time autoregulation monitoring using near-infrared spectroscopy may provide a more rational basis for individualizing blood pressure to measure injurious hypotension (mean < 45 mmHg) [18] and perioperative stroke [16] during CPB. Precise diagnostic tools can be leveraged to deliver personalized treatments and provide prognostic improvements regarding postoperative morbidity and mortality in cardiac surgery [10,11]. A relative 20% reduction of the baseline value or an absolute value lower than 50% is a suggested threshold for intervention [19][20][21].…”
Section: Personalized Cerebral Oximetry Monitoring During Hypothermic...mentioning
confidence: 99%
“…The duration and magnitude of blood pressure below the autoregulation threshold were independently associated with major morbidity or operative mortality after cardiac surgery [10]. Therefore, regional cerebral oximetry monitoring has been recommended during cardiothoracic surgery [11] and applied to guide nitroglycerin infusion during controlled hypotension for major open urological or abdominal surgery [12].…”
Section: Introductionmentioning
confidence: 99%